2018
DOI: 10.1007/s11136-018-2047-5
|View full text |Cite
|
Sign up to set email alerts
|

A new scale for measuring quality of life in acquired brain injury

Abstract: This is the post-print version of a paper published in Quality of Life Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The assessment of QoL was carried out through the administration of the CAVIDACE scale (Fernández et al, 2018, Verdugo et al, 2018), which is a disease-specific instrument aimed to assess the QoL-related personal outcomes of adults with ABI. The scale has shown excellent evidences of validity and reliability (Fernández et al, 2019), and it has a suitable internal consistency (alpha ordinal values ranged from .81 to .93) and high inter-rater reliability (ICC = .97). The analysis of construct validity supported the eight correlated factors model (TLI = .87; CFI = .89; RMSEA = .06; SRMR = .07).…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of QoL was carried out through the administration of the CAVIDACE scale (Fernández et al, 2018, Verdugo et al, 2018), which is a disease-specific instrument aimed to assess the QoL-related personal outcomes of adults with ABI. The scale has shown excellent evidences of validity and reliability (Fernández et al, 2019), and it has a suitable internal consistency (alpha ordinal values ranged from .81 to .93) and high inter-rater reliability (ICC = .97). The analysis of construct validity supported the eight correlated factors model (TLI = .87; CFI = .89; RMSEA = .06; SRMR = .07).…”
Section: Methodsmentioning
confidence: 99%
“…There is now a focus on creating a context for wellbeing that spans beyond attempts to simply eradicate or reduce impairment. For example, developments in QoL literature for those living with ABI emphasize the need for more comprehensive assessments that include social inclusion, community integration, human rights and personal development (Fernández et al, 2019). This psychosocial approach to assessment reaches beyond disease-specific assessments (Sánchez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The RMSEA revealed that the proposed model reached optimal values. The fit of the model was substantially better than that of its confirmatory counterpart (RMSEA = 0.08), suggesting that setting all factor loadings to zero in the confirmatory model led to an accumulation of small errors of specification with high impact on model it (Fernández et al, 2018). The construct validity was therefore deemed satisfactory.…”
Section: Resultsmentioning
confidence: 99%